Application of Social Cognitive Theory to Promote Healthy Behavior Among the Elderly at Integrated Health Post for Elderly - Agil Rafi’ah Afandi; Argyo Demartoto; Bhisma Murti (Journal of Health Promotion and Behavior, 2025)
Background: The results of a survey by the Central Statistics Agency in 2021 reported that as many as 42.22% of the elderly population in Indonesia experience health problems. One of the factors that determines healthy behavior in the elderly is implementing healthy behavior. This study aims to examine the application of social cognitive theory as a determinant of healthy behavior of the elderly in Sukoharjo Regency, Central Java. Subjects and Method: This was a cross-sectional study carried out at integrated health post (posyandu) in Grogol, Sukoharjo Regency, Central Java, in June-July 2024. A sample of 200 elderly was selected purposively. Five villages were randomly selected. From each village, 6 primary strata Posyandu, 6 intermediate strata Posyandu, 6 purnama strata Posyandu, and 7 independent Posyandu were chosen. Then, from each selected Posyandu, 8 elderly individuals were randomly selected. The dependent variable is healthy behavior in the elderly. The independent variables are a number of constructs in social cognitive theory, namely observational learning, outcome expectation, outcome expectancy, reinforcement, and self-efficacy. Data were analyzed by multiple linear regression. Results: Healthy behaviors increased with observational learning (b= 0.17; 95% CI= 0.12 to 0.43; p= 0.001), outcome expectation (b=0.24; 95% CI= 0.02 to 0.473; p= 0.036), outcome expectancy (b= 0.36; 95% CI= 0.05 to 0.68; p= 0.025), reinforcement (b= 0.36; 95% CI= 0.10 to 0.84; p= 0.013),  and self efficacy (b= 0.55; 95% CI= 0.19 to 0.91; p= 0.003). Conclusion: Healthy behavior in the elderly is positively associated with observational learning, outcome expectation, outcome expectancy, reinforcement, and self efficacy.